Identification of OqxB Efflux Pump and Tigecycline Resistance Gene Cluster tmexC3D2-toprJ3 in Multidrug-Resistant Pseudomonas Stutzeri Isolate G3 - Amande TJ; Kaszyk V; Brown F (Infection and Drug Resistance, 2025)
Tivkaa Joseph Amande,1,2 Vanessa Kaszyk,2 Fiona Brown2 1School of Life and Health Sciences, University of Roehampton, London, UK; 2Department of Biological Sciences, University Centre Peterborough, Part of Inspire Education Group, Peterborough, UKCorrespondence: Tivkaa Joseph Amande, School of Life and Health Sciences, Parkstead House, Whitelands College, University of Roehampton, London, SW15 4JD, UK, Tel +44 (0)20 8392 3531, Email tivkaa.amande@roehampton.ac.ukPurpose: To identify antibiotic resistance genes (ARGs) and understand the molecular basis of multidrug resistance in P. stutzeri isolate G3.Methods: Whole-genome sequencing of isolate G3 was conducted at 30X coverage using Illumina NovaSeq 6000. Reads were trimmed using Trimmomatic and assessed using a combination of scripts that incorporated Samtools, BedTools, and bwa-mem. De novo assembly was performed using SPAdes, and assembly metrics were evaluated using QUAST. The assembled genome was uploaded to a Type Strain Genome Server (TYGS) for taxonomic identification. Genome annotation was performed using the KBase and Proksee software using PROKKA. ARGs were identified using the Comprehensive Antibiotic Resistance Database (CARD).Results: P. stutzeri isolate G3 demonstrated resistance to most antibiotics tested, including meropenem (10 μg), ciprofloxacin (5 μg), gentamicin (10 μg), and tetracycline (30 μg). The ARGs identified were PmpM, AdeF, rsmA, vgb(A), BcI, cipA, OCH-2, and tet(45). A tigecycline-resistant gene cluster, tmexC3D2-toprJ3, was found in NODE_84, while the oqxB gene, encoding a resistance-nodulation-division (RND) efflux pump, was in NODE_309. Phylogenetic analysis showed OqxB clustered with Pseudomonas species, distinct from Klebsiella and Enterobacter. Comparative analysis of oqxB revealed P. stutzeri isolate G3 shared 78– 100% identity with Pseudomonas aeruginosa strain 1334/14 in key components of the multidrug efflux system, including the transcriptional regulator MexT, periplasmic adaptor subunit MexE, and permease subunit MexF.Conclusion: Our findings offer new insights into the reservoir of ARGs in the draft genome of Pseudomonas stutzeri isolate G3, including the tmexC3D2-toprJ3 and oqxB genes, highlighting its genomic plasticity and public health significance. This adaptability enables P. stutzeri to thrive in clinical environments, despite its natural habitat association. This study advances our understanding of the molecular mechanisms driving resistance in P. stutzeri and offers valuable insights to inform strategies for combating the spread of antimicrobial resistance in clinical and environmental settings.Keywords: Pseudomonas stutzeri, OqxB RND efflux pump, tmexC3D2-toprJ3, antibiotic resistance genes, bacterial genomics, whole-genome sequencing